Reducing Distortions in International Commodity Markets : an Agenda for Multilateral Cooperation - Hoekman, Bernard; Martin, Will (World Bank, Washington, DC, 2017)
World commodity markets-and particularly the markets for agricultural commodities-remain highly distorted despite the wave of liberalization that has swept world trade since the 1980s. Some markets for commodities are characterized by imperfect competition. Where monopolies or oligopolies in trade arise either because of government regulation or through other barriers to entry, distortions may arise that call for the application of antitrust law and other forms of pro- competitive policy action. Commodity markets are distorted on both the export and the import sides, with serious implications for world prices and their volatility. Governments also have a long history of intervening in markets for other natural resources, both renewable and non-renewables. Protection rates for imports of non-agricultural natural resources are generally low because of pressure from user industries. However, importing countries confronting exporters of resources with market power and thus the ability to affect world prices may seek to use import tariffs or excise taxes to lower demand and shift rents away from supplying nations. In sum, a wide mix of policy instruments is used by countries to influence the level and volatility of domestic prices for commodities. Countries also pursue policies that may affect international prices, either indirectly or directly, if they are large suppliers or importers.